Reading Comprehension Levels: The impact of audiovisual material on English as a foreign language learners - Briceño Nuñez, Chess Emmanuel (2024)
This study explores the impact of audiovisual material on the reading comprehension of English as a foreign language students. Employing a correlational approach with a quasi-experimental design, two secondary education groups were assessed. The experimental group, exposed to videos, outperformed the control group in reading comprehension levels, particularly in inferential understanding. The methodology included written tests and qualitative observations. Results underscore a general improvement in the performance of the group exposed to audiovisual material, supporting the efficacy of this strategy in English language teaching. The study concludes that the use of audiovisual material improves reading comprehension in students of English as a foreign language, evidencing higher performance and participation. However, limitations in the study design and evaluation are noted, suggesting the inclusion of additional methods for a more complete understanding in future research.